Analisis Kesesuaian Penempatan Kerja, Beban Kerja Terhadap Prestasi Karyawan Pada Bank 9 Syariah Jambi - Toyba Toyba; Titin Agustin Nengsih; Refky Fielnanda (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
Employee performance as one of the values ​​and control of human resources is a complex value possessed by employees that can be influenced by various things which can increase employee performance and can reduce the value of employee performance which can be detrimental to the company. This study aims to determine the effect of employee placement on employee performance, workload on employee performance, and employee placement, workload on employee performance that occurs at bank 9 syari'ah Jambi. The results of the research conducted show that (1) work placement has a positive but not significant effect on employee work performance at bank 9 syari'ah Jambi. (2) workload has a positive but not significant effect on employee performance at bank 9 Jambi syari'ah.